Etude de l’activité antimicrobienne des bactéries lactiques vis-à-vis des bactéries pathogènes. - BEN MANSOUR, Samra; BELARBI, Fatiha (My University, 2025)
Lactic acid bacteria, widely present in fermented foods such as yogurt, sauerkraut, cheese and in the intestinal microbiota, are increasingly being studied for their beneficial effects on health. One of their most interesting roles is their ability to fight pathogenic bacteria through the unique ability to synthesize inhibitory substances. Our study initially focused on: the isolation of lactic strains from natural yogurt and the identification of the 08 strains isolated and purified by F. Attoura from lben (cow), through physiological, biochemical tests, and macro and microscopic observation. Next, the antimicrobial activity of the lactic acid strains against pathogenic bacteria: Pseudomonas aeruginosa ATCC27853, Staphylococcus aureus ATCC25923, was studied using the double-layer method. To determine the response of lactic acid strains to various antibiotics, we examined their resistance using the diffusion method on solid MRS with antibiotic disks. The results of our study of inhibitory interactions allowed us to indicate that these lactic acid strains are suitable for medical use against pathogenic bacteria, as well as for food biopreservation, as they possess good antimicrobial activity against pathogenic bacteria.
Keywords: Lactic acid bacteria, pathogenic bacteria, inhibitory substances, antimicrobial activity, lben